Factors influencing the intention to use and support to change to mobile training among employees of Sharjah Police general command in ministry of interior at the UAE - Alzarooni, Mohamed Omar Abbas Ali (2023)
Mobile training is still at an early stage of implementation and adoption in the public sector of the United Arab Emirates. The success of transitioning to a mobile training system depends on user support, acceptance, and the decision to embrace mobile training. This study aims to investigate the factors influencing the intention to use and support the shift towards mobile training within the Sharjah Police General Command in the UAE. The study employs the third version of the Unified Theory of Acceptance and Use of Technology (UTAUT3) as its theoretical basis, given its flexibility in adopting multi-level models. The proposed conceptual framework includes Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Individual Beliefs (attitude) (IB), Mobile Training Infrastructure (MTI), Training Unit Professionalism (TUP), Management Support (MS), Facilities Condition (FC), Technology Habits (TH), Legacy System Habits (LSH), Habits (HA), Intention to Use Mobile Training (IUMT), and support to change to mobile training (SCMT). The study employs quantitative methods, using primary data collected through a well-structured questionnaire. The target population comprises all staff member of the General Department of Sharjah Police in the Emirate of Sharjah, totaling 7,715 employees. A sample size of 367 individuals was selected using a quota sampling technique. Ultimately, data from 373 respondents across 19 different departments were included in the final dataset. The study investigates 18 different hypotheses. Based on the path coefficient, the results indicate that individual belief has the highest impact on the intention to use mobile training (0.464), followed by facilitating conditions (0.260), and habit (0.252). Regarding the predictors of support for change to mobile training, the intention to use mobile training has the most significant impact (0.711), followed by individual belief (0.099). The results also reveal that facilities conditions (FC) and habit (HA) do not have a significant impact on support for change to mobile training (SCMT). The findings of this thesis suggest that attitude has the highest impact, followed by facilitating conditions; therefore, policymakers should promote performance and effort expectancy, in addition to social influence. Future research could explore the rejected relationships between habit and facilitating conditions, as well as replicating the proposed model in different contexts.